Cross-Cultural Adaptation, Reliability, and Validity of the Revised Korean Version of Ruminative Response Scale - Lee, Seonyoung (Korean Neuropsychiatric Association, 2014)
OBJECTIVE: Rumination is a negative coping strategy defined as repetitive and passive focusing on negative feelings such as depression. The Ruminative Response Scale (RRS) is a widely-used instrument to measure rumination, but there is continuing argument about the construct validity of the RRS, because of probable overlap between the measurement of depression and that of rumination. The RRS-Revised (RRS-R), which removed 12 items of the RRS, is suggested as a more valid instrument for measuring rumination. Therefore, we translated RRS-R into Korean and explored the reliability, validity and factor structure in patients with major depressive disorders. METHODS: Seventy-nine patients with major depressive disorder took the Korean version of RRS, RRS-R, State Trait Anxiety Inventory, Beck Depression Inventory and Penn State Worry Questionnaire. We performed exploratory factor analysis of RRS-R, and tested construct validity, internal reliability and test-retest reliability. RESULTS: The internal and test-retest reliability of RRS-R was high. Factor analysis revealed that RRS-R is composed of two factors. 'Brooding' factor explained 56.6% and 'Reflection' factor explained 12.5%. RRS-R, especially 'Brooding factor', was highly correlated with other clinical symptoms such as depression, anxiety and worry. CONCLUSION: In this study, we find out the RRS-R is more reliable and valid than the original RRS in Korean patients with depression because the RRS-R is free from the debate about the overlap of item with BDI. We also revealed that 'Brooding' is highly correlated with depressive symptoms. RRS-R may be a useful instrument to explore the implication of 'Brooding' in depression.